Software source code escrow agreement and legal obstacles of its execution - Štorha, Madara (Riga Graduate School of Law, 2020)
Software source code escrow agreement is a relatively new occurrence, emerged together with the rise of software industry in 1970’s in the U.S. Taking into account the fact that business relationships between the software licensor and the licensee are mostly permanent, i.e. significant part is not only the license agreement, but also maintenance and support service duties assumed by the licensor, it is important that business continuity of the licensee is ensured. Software source code escrow agreement aims to provide this assurance by promise, that if the licensor ceases to exist (becomes insolvent), then the source code – building instruction of the software, will be turned over to the licensee and provide licensee with the option to maintain the software himself. Thesis is dedicated to enquiry what obstacles impede execution of such contract and the answer lies in the consideration why the software escrow agreement is concluded in the first place – bankruptcy. That is to say, mandatory bankruptcy laws preclude any actions following the commencement of bankruptcy proceedings if they concern property of bankruptcy estate.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Private law::Commercial and company law; Contract law; Software license